How to win at chess : the ultimate guide for beginners and beyond - Rozman, Levy (Emeryville : Ten Speed Press, 2023)
"Learn chess from International Master and YouTube's top chess teacher Levy Rozman (aka GothamChess) in this refreshing and fun guide for beginner and intermediate players"-- |c Provided by publisher.
Keywords: Chess